10 PHILADELPHIA CHROMOSOME MOSAICISM DUE TO ADDITIONAL CYTOGENETIC ABNORMALITIES IN CHRONIC MYELOID LEUKEMIA MIGHT ADVERSELY AFFECT PROGNOSIS AND RESPONSE TO IMATINIB. (1st March 2007) - Landstrom, A.; Ketterling, R.; Knudson, R.; Dewald, G.; Tefferi, A.
Abstract : Background: Chronic myeloid leukemia (CML) is invariably associated with the reciprocal translocation of BCR and ABL to form the Philadelphia chromosome (Ph), t(9;22)(q34;q11). At diagnosis, a small proportion of patients display additional cytogenetic abnormalities and/or a variable proportion of cytogenetically normal metaphases that coexist with Ph-positive metaphases. The objective of the current study was to examine the prognostic relevance and therapy implications of this scenario. Methods: The study population consisted of 65 (47.7% female) consecutive, newly diagnosed, untreated CML patients seen at the Mayo Clinic with a median age of 59 years; 44.5% were initially treated with interferon (IFN)-α, resulting in complete cytogenetic remission in 10.7%, for a median length of 5.83 years, whereas partial cytogenetic remission was achieved in 3.57%, for a median length of 2 years; 55.5% were treated with imatinib (Gleevec), resulting in complete cytogenetic remission in 54.1%, for a median length of 3.08 years, whereas partial cytogenetic remission was achieved in 13.5%, for a median length of 1.08 years. All statistical analysis was completed using SAS software (SAS Inc., Cary, NC), and statistical significance was set at the level of p ≤ .05. Results: Survival at 5 years through Kaplan-Meier analysis was approximately 92% in patients demonstrating only the Ph chromosome ( n = 53) versus 60% in patients with additional chromosomal abnormalities ( n = 12; p < .0001 through log rank and Breslow-Gehan-Wilcox analysis). In addition, patients with additional chromosomal abnormalities demonstrated lower rates of either complete or partial cytogenetic remission with imatinib therapy. Similarly, the 5-year survival rate of patients with less than 90% Ph-positive metaphases at diagnosis ( n = 4) was approximately 60% compared with 92% in patients with greater than 90% Ph-positive metaphases ( n = 61; p = .01 by log rank and p = .001 by Breslow-Gehan-Wilcox analysis). Additionally, the former group of patients was significantly less responsive to imatinib. Finally, there was significant correlation between Ph-positive metaphase mosaicism and the presence of additional chromosomal abnormalities ( p = .05). Conclusion: Although it is tempting to speculate that Ph-chromosome mosaicism and/or additional cytogenetic abnormalities at presentation of CML is a surrogate for the presence of Ph-negative imatinib-resistant clones, the preliminary results from the current study require validation from a larger study, which is currently under way. It is possible that patients who present with less than 90% Ph-positive metaphase cells at diagnosis may harbor chromosomal abnormalities in other metaphase cells that are undetectable by conventional cytogenetics. Indeed, this clonal population might be resistant to imatinib therapy and negatively impact survival.